Quantitative trait loci and genomic prediction for grain sugar and mineral concentrations of cowpea [Vigna unguiculata (L.) Walp.] - Huynh, B.L.; Stangoulis, J.C.R.; Vuong, T.D.; Shi, H.; Nguyen, H.T.; Duong, T.; Boukar, O.; Kusi, F.; Batieno, B.J.; Cisse, N.; Diangar, M.M.; Awuku, F.J.; et al. (2024)
Development of high yielding cowpea varieties coupled with good taste and rich in essential minerals can promote consumption and thus nutrition and profitability. The sweet taste of cowpea grain is determined by its sugar content, which comprises mainly sucrose and galacto-oligosaccharides (GOS) including raffinose and stachyose. However, GOS are indigestible and their fermentation in the colon can produce excess intestinal gas, causing undesirable bloating and flatulence. In this study, we aimed to examine variation in grain sugar and mineral concentrations, then map quantitative trait loci (QTLs) and estimate genomic-prediction (GP) accuracies for possible application in breeding. Grain samples were collected from a multi-parent advanced generation intercross (MAGIC) population grown in California during 2016–2017. Grain sugars were assayed using high-performance liquid chromatography. Grain minerals were determined by inductively coupled plasma–optical emission spectrometry and combustion. Considerable variation was observed for sucrose (0.6–6.9%) and stachyose (2.3–8.4%). Major QTLs for sucrose (QSuc.vu-1.1), stachyose (QSta.vu-7.1), copper (QCu.vu-1.1) and manganese (QMn.vu-5.1) were identified. Allelic effects of major sugar QTLs were validated using the MAGIC grain samples grown in West Africa in 2017. GP accuracies for minerals were moderate (0.4–0.58). These findings help guide future breeding efforts to develop mineral-rich cowpea varieties with desirable sugar content.